An analysis of teaching and learning partnerships in Australian universities: prevalence, typology and influences. Issue 4 (3rd July 2020) - Fox, Jillian L.; Diezmann, Carmel M.
ABSTRACT: Teaching and learning partnerships in universities have the potential to enhance the interconnections and interdependencies between higher education, society and the economy for the benefit of all stakeholders. The aim of this paper was to investigate five representative Australian universities' engagement in teaching and learning partnerships identifying the prevalence, type and influences. The two data sources were each university's Mission-based Compact and their strategic plans. A total of 134 statements in the Compacts related to teaching and learning partnerships and these statements related to eight themes. These teaching and learning partnerships within a particular time period were influenced by industry–community relationships, accreditation requirements, and the broader social environment. Whilst all universities in the study acknowledge the significance of teaching and learning partnerships, it is the depth and breadth of these teaching and learning partnerships that create distinctions among the universities.